Pengaruh Lingkungan Kerja, Kompetensi dan Komunikasi Terhadap Motivasi Kerja dan Dampaknya Pada Kinerja Pegawai Tahun 2021 pada Kantor Pusat Produksi, Inspeksi dan Sertifikasi Hasil Perikanan Provinsi DKI Jakarta - Arief Prakoso; Suryono Efendi (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study analyzes the influence of the Work Environment, Competence and Communication on Work Motivation and its impact on Employee Performance in 2021 at Kantor Pusat Produksi, Inspeksi dan Sertifikasi Hasil Perikanan Provinsi DKI Jakarta. Hypothesis testing in this study used a statistical analysis tool Structural Equation Modeling (SEM). The results showed that the Work Environment and Communication had a positive and significant effect on Employee Motivation, Competence had a positive and insignificant effect on Employee Motivation. Work Environment has a negative and insignificant effect on Employee Performance, Competence has a positive and insignificant effect on Employee Performance, Communication has a negative and significant effect on Employee Performance. Work Environment has a significant effect on Employee Performance through Employee Motivation, Competence has no significant effect on Employee Performance through Employee Motivation, Communication has a significant effect on Employee Performance through Employee Motivation. Employee Motivation has a positive and significant effect on Employee Performance.